Simulation of laser-driven, ablated plasma flows in collisionless shock experiments on OMEGA and the NIF - Grosskopf, M; Drake, R; Kuranz, C; Rutter, E; Ross, J; Kugland, N; Plechaty, C; Remington, B; Spitkovsky, A; Gargate, L; Gregori, G; Bell, A; et al. (2013)
Experiments investigating the physics of interpenetrating, collisionless, ablated plasma flows have become an important area of research in the high-energy-density field. In order to evaluate the feasibility of designing experiments that will generate a collisionless shock mediated by the Weibel instability on the National Ignition Facility (NIF) laser, computer simulations using the Center for Radiative Shock Hydrodynamics (CRASH) radiation-hydrodynamics model have been carried out. This paper reports assessment of whether the experiment can reach the required scale size while maintaining the low interflow collisionality necessary for the collisionless shock to form. Comparison of simulation results with data from Omega experiments shows the ability of the CRASH code to model these ablated systems. The combined results indicate that experiments on the NIF are capable of reaching the regimes necessary for the formation of a collisionless shock in a laboratory experiment. © 2013.